2012
DOI: 10.3126/sw.v10i10.6869
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in bulk and particle size fractions from street dust of Kathmandu city as the possible basis for risk assessment

Abstract: Street dust has been sampled from eight major locations of Kathmandu city. The samples were separated into three particle size fractions (<425, 425-600 and >600 μm) and analyzed for Pb, Cu, Zn and Fe using Atomic Absorption Spectrophotometric method. Results revealed that the bulk samples as well as all particle size fractions under investigation were found to have the metal abundance order as Fe > Zn > Cu > Pb. However, the trace metal concentrations increased with the decrease of dust particle size in all sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…This is consistent with the findings of Herath et al (2013) who also reported high organic matter content in Colombo metropolitan region due waste disposal, leakage of lubricants and vehicle oil. Further, the present study is also in agreement with the work of Karmacharya and Shakya (2012) and Acosta et al (2011) who reported similar results in properties of street dust.…”
Section: Dust Propertiessupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the findings of Herath et al (2013) who also reported high organic matter content in Colombo metropolitan region due waste disposal, leakage of lubricants and vehicle oil. Further, the present study is also in agreement with the work of Karmacharya and Shakya (2012) and Acosta et al (2011) who reported similar results in properties of street dust.…”
Section: Dust Propertiessupporting
confidence: 93%
“…Results revealed that dust particle size of 425-150 µm was the main dominant fraction in all the studied areas and varied from 49.17 % (urban) to 56.53 % (residential) of the total fraction. This finding is also supported by the work of Karmacharya and Shakya (2012) who reported dust particle of 425-150 µm mesh size as the major fraction by percentage in street dust. However, the composition of dust may vary depending on climate, human activities, soils and rocks of the surrounding areas etc (Amato et al 2010).…”
Section: Distribution Of Dust In Particle Size Fractionssupporting
confidence: 83%
See 1 more Smart Citation
“…The ingestion of dust particles with high concentration of potentially toxic metals, possess a potential threat to human health. For instance, in California, 5-10% of allergen city for atmospheric total suspended particulate matter was attributed to paved road dust emissions [10]. Heavy metals are persistent pollutant that can be biomagnified in the food chain, becoming increasingly dangerous to humans and wild life.…”
Section: Introductionmentioning
confidence: 99%